2004
DOI: 10.1172/jci21655
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil protein kinase Cδ as a mediator of stroke-reperfusion injury

Abstract: Thrombolysis is widely used to intervene in acute ischemic stroke, but reestablishment of circulation may paradoxically initiate a reperfusion injury. Here we describe studies with mice lacking protein kinase Cδ (PKCδ) showing that absence of this enzyme markedly reduces reperfusion injury following transient ischemia. This was associated with reduced infiltration of peripheral blood neutrophils into infarcted tissue and with impaired neutrophil adhesion, migration, respiratory burst, and degranulation in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 55 publications
6
68
0
Order By: Relevance
“…PKC-a was further implicated in fMLP-and PMA-induced superoxide generation based on siRNA evidence in HL-60 cells differentiated to resemble granulocytes (Korchak et al 2007). Brown et al (2003) substantiated the role of PKC-d in NADPH oxidase activation and superoxide generation in neutrophils after stimulation with PMA, and Chou et al (2004) showed a marked decrease of TNF-a-induced superoxide production in PKC-d gene deficient neutrophils.…”
Section: Oxidative Burstmentioning
confidence: 62%
See 4 more Smart Citations
“…PKC-a was further implicated in fMLP-and PMA-induced superoxide generation based on siRNA evidence in HL-60 cells differentiated to resemble granulocytes (Korchak et al 2007). Brown et al (2003) substantiated the role of PKC-d in NADPH oxidase activation and superoxide generation in neutrophils after stimulation with PMA, and Chou et al (2004) showed a marked decrease of TNF-a-induced superoxide production in PKC-d gene deficient neutrophils.…”
Section: Oxidative Burstmentioning
confidence: 62%
“…As described in the previous section, reduced adhesion of PKC-d gene deficient neutrophils after GPCR ligand activation in vitro could be caused by defective signaling downstream of integrin engagement (Chou et al 2004). Evidence for the involvement of PKC isoforms in integrin-dependent outside-in signaling comes from platelets, in which fibrinogen binding causes spreading via outside-in signaling downstream of adhesion via the platelet integrin a IIb b 3 .…”
Section: Adhesion Strengthening and Crawlingmentioning
confidence: 87%
See 3 more Smart Citations